2021
DOI: 10.1111/ddg.14526
|View full text |Cite
|
Sign up to set email alerts
|

Rat bite fever, a diagnostic challenge: case report and review of 29 cases

Abstract: Summary Rats can transmit Streptobacillus moniliformis, which may cause rat‐bite fever (RBF), a rare and potentially lethal zoonosis. Fastidious in vitro growth and unspecific symptoms, including fever, arthralgia, and polymorphous skin lesions, complicate the diagnosis. Rat‐bite fever follows exposure to contaminated bodily fluids of infected rodents; however, reports on Streptobacillus moniliformis‐related infections are few so far. A female patient presented with painful hemorrhagic pustules and purpuric le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 17 publications
0
5
1
1
Order By: Relevance
“…As shown in the present case, this method accurately identified S. moniliformis. In our review of recent case report on RBF infections, we found most cases were identified by 16S-rRNA sequencing (2,6,11). The pathogen was not confirmed by sequencing analyses in the present case, which may be a limitation in the present case.…”
Section: Discussioncontrasting
confidence: 62%
See 4 more Smart Citations
“…As shown in the present case, this method accurately identified S. moniliformis. In our review of recent case report on RBF infections, we found most cases were identified by 16S-rRNA sequencing (2,6,11). The pathogen was not confirmed by sequencing analyses in the present case, which may be a limitation in the present case.…”
Section: Discussioncontrasting
confidence: 62%
“…RBF is a low incidence of the disease with non-specific symptoms, as for this clinicist make a direct clinical diagnosis virtually impossible. In our review of case reports on RBF infections, we found in most cases accurate diagnostic delays caused up to seven days of significant delays to the initiating pathogen-specific therapy (6). More than 50% of patients with RBF develop migratory polyarthralgias, involving the small and large joints of the extremities (1) and may also be accompanied by septic arthritis (7).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations